Adaptation to new complete dentures: is the neuromuscular system outcome-oriented or effort-oriented? - Eberhard, Lydia; Oh, Keunyoung; Eiffler, Constantin; Rammelsberg, Peter; Kappel, Stefanie (Clinical oral investigations, 2018)
ObjectiveThe aim of this study was to observe the adaptation strategy of the stomatognathic system during the adaptation of complete dentures, comprising masticatory parameters and subjective measures. Our hypothesis was that with new dentures, masticatory performance would increase while the effort of the system is kept constant.Material and methodsThirty-two patients received standardized new complete dentures. Masticatory performance tests were conducted with old dentures (T1), immediately after incorporation of new dentures (T2) and after an adaptation period of 3 months (T3). Patients habitually chewed the silicone-based artificial test food Optocal. The comminuted test food was analyzed and mean particle sizes (x50) were calculated. Simultaneously, surface EMGs of the anterior temporalis and masseter muscles were recorded. Specific (SMW) and total muscle work (TMW) were determined. Patients filled in the OHIP-49 questionnaire. Test conditions were compared using repeated-measures ANOVA with SPSS 22 (SPSS Inc.)ResultsMasticatory performance increased (P = 0.016) between old (x50 = 4.99 ± 0.28) and adapted new dentures (x50 = 4.80 ± 0.33). TMW deteriorated (P = 0.004) at T2 (from TMW1 = 119.77 ± 56.49 to TMW2 = 92.12 46.27), and increased again (P = 0.028) at T3 (TMW3 = 107.66 ± 44.65). OHIP scores decreased significantly in all subscales (P < 0.001…P = 0.046); the total score was reduced (P < 0.001) from 56.24 ± 29.05 (T1) to 34.66 ± 24.74 (T3).ConclusionIn complete denture wearers, masticatory performance improves over an adaptation period. Muscle work initially decreased before reaching its original level again after adaptation. Subjective parameters overestimated the functional improvements.Clinical significanceThe subjective evaluation does not adequately reflect functional improvements. The assessment of function requires an adaptation period.